MAIN ECONOMIC PROBLEMS OF SMALL BUSINESS IN RUSSIA AND THE WAYS OF THEIR SOLUTIONS - Elena Shidakova (Вестник Северо-Кавказского федерального университета, 2022)
This article discusses the current problems of Russian small businesses. The issues related to the positive impact of enterprises on the economy of the state, the analysis of the situation of small business in Russia, the difficulties and barriers that arise in the way of business development, as well as possible ways of overcoming emerging problems are suggested.